Direct noninvasive estimation of myocardial tricarboxylic acid cycle flux in vivo using hyperpolarized 13C magnetic resonance. (October 2015) - Bastiaansen, Jessica A.M.; Cheng, Tian; Lei, Hongxia; Gruetter, Rolf; Comment, Arnaud
Abstract: Background: The heart relies on continuous energy production and imbalances herein impair cardiac function directly. The tricarboxylic acid (TCA) cycle is the primary means of energy generation in the healthy myocardium, but direct noninvasive quantification of metabolic fluxes is challenging due to the low concentration of most metabolites. Hyperpolarized 13 C magnetic resonance spectroscopy (MRS) provides the opportunity to measure cellular metabolism in real time in vivo. The aim of this work was to noninvasively measure myocardial TCA cycle flux (VTCA ) in vivo within a single minute. Methods and results: Hyperpolarized [1- 13 C]acetate was administered at different concentrations in healthy rats. 13 C incorporation into [1- 13 C]acetylcarnitine and the TCA cycle intermediate [5- 13 C]citrate was dynamically detected in vivo with a time resolution of 3 s. Different kinetic models were established and evaluated to determine the metabolic fluxes by simultaneously fitting the evolution of the 13 C labeling in acetate, acetylcarnitine, and citrate. VTCA was estimated to be 6.7 ± 1.7 μmol · g − 1  · min − 1 (dry weight), and was best estimated with a model using only the labeling in citrate and acetylcarnitine, independent of the precursor. The TCA cycle rate was not linear with the citrate-to-acetate metabolite ratio, and could thus not be quantified using a ratiometric approach. The 13 C signal evolution of citrate, i.e. citrate formation was independent of the amount of injected acetate, while the 13 C signal evolution of acetylcarnitine revealed a dose dependency with the injected acetate. The 13 C labeling of citrate did not correlate to that of acetylcarnitine, leading to the hypothesis that acetylcarnitine formation is not an indication of mitochondrial TCA cycle activity in the heart. Conclusions: Hyperpolarized [1- 13 C]acetate is a metabolic probe independent of pyruvate dehydrogenase (PDH) activity. It allows the direct estimation of VTCA in vivo, which was shown to be neither dependent on the administered acetate dose nor on the 13 C labeling of acetylcarnitine. Dynamic 13 C MRS coupled to the injection of hyperpolarized [1- 13 C]acetate can enable the measurement of metabolic changes during impaired heart function. Graphical abstract: Highlights: Acetate metabolism was measured by hyperpolarized MR in healthy myocardium in vivo. Dynamic detection of citrate formation enabled the estimation of TCA cycle flux. In vivo TCA cycle flux was estimated from a single minute experiment. 13 C labeling of acetylcarnitine does not relate to TCA cycle activity. The estimated TCA cycle flux was independent of administered acetate dose.